2003
DOI: 10.1002/jemt.10383
|View full text |Cite
|
Sign up to set email alerts
|

Collecting, shipping, storing, and imaging snow crystals and ice grains with low‐temperature scanning electron microscopy

Abstract: Methods to collect, transport, and store samples of snow and ice have been developed that enable detailed observations of these samples with a technique known as low-temperature scanning electron microscopy (LTSEM). This technique increases the resolution and ease with which samples of snow and ice can be observed, studied, and photographed. Samples are easily collected in the field and have been shipped to the electron microscopy laboratory by common air carrier from distances as far as 5,000 miles. Delicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Domine et al (2003) may have observed growth steps on surface hoar crystals studied by scanning electron microscopy (SEM), and whose height was about 1 µm, but it is not even totally certain that the structures observed were growth steps, and they did not seem to originate from a crystal edge, but rather from a grain boundary, so that the representativity of this observation may be limited. Indeed, the numerous SEM studies of snow crystals (Wergin et al, 1996;Domine et al, 2003;Erbe et al, 2003;Legagneux et al, 2003) usually do not show any structures that can be convincingly attributed to growth steps, which suggest that these could be undetectable by SEM and much smaller than 1 µm in most cases.…”
Section: Application To Snowpacks and Cloudsmentioning
confidence: 99%
“…Domine et al (2003) may have observed growth steps on surface hoar crystals studied by scanning electron microscopy (SEM), and whose height was about 1 µm, but it is not even totally certain that the structures observed were growth steps, and they did not seem to originate from a crystal edge, but rather from a grain boundary, so that the representativity of this observation may be limited. Indeed, the numerous SEM studies of snow crystals (Wergin et al, 1996;Domine et al, 2003;Erbe et al, 2003;Legagneux et al, 2003) usually do not show any structures that can be convincingly attributed to growth steps, which suggest that these could be undetectable by SEM and much smaller than 1 µm in most cases.…”
Section: Application To Snowpacks and Cloudsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) has long been recognized as an attractive alternative for observing ice morphology (Cross, 1968;Rango et al, 2000;Erbe et al, 2003), because of its resolution and depth of field. However, the high vacuum conditions and coating procedures usually employed to prepare samples do not permit observation of surface dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore estimate that the overall uncertainty of SSA measurement of wet snow using DUFISSS is at the most 11 %, if the LWC is not known. Finally, SSA can also be defined as the surface area per unit volume of ice or water, rather than per unit mass of snow (Fierz et al, 2009). It is then conveniently expressed in mm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding (2), the work of Brzoska et al (1998) showed that snow subjected to flash freezing, a process much more prone to produce structural changes than the slow freezing used here, did not lead to any detectable structural change. Furthermore, scanning electromicrographs by Erbe et al (2003) (their Fig. 9) and Wergin et al (1995) (their Fig.…”
Section: Experimental Protocolmentioning
confidence: 99%